Glycerol Monolaurate Ameliorated Intestinal Barrier and Immunity in Broilers by Regulating Intestinal Inflammation, Antioxidant Balance, and Intestinal Microbiota - Kong, Linglian; Wang, Zhenhua; Xiao, Chuanpi; Zhu, Qidong; Song, Zhigang (Frontiers in Immunology, 2021)
This study was conducted to investigate the impact of glycerol monolaurate (GML) on performance, immunity, intestinal barrier, and cecal microbiota in broiler chicks. A total of 360 one-day-old broilers (Arbor Acres) with an average weight of 45.7 g were randomly allocated to five dietary groups as follows: basal diet and basal diets complemented with 300, 600, 900, or 1200 mg/kg GML. Samples were collected at 7 and 14 days of age. Results revealed that feed intake increased (P < 0.05) after 900 and 1200 mg/kg GML were administered during the entire 14-day experiment period. Dietary GML decreased (P < 0.05) crypt depth and increased the villus height-to-crypt depth ratio of the jejunum. In the serum and jejunum, supplementation with more than 600 mg/kg GML reduced (P < 0.05) interleukin-1β, tumor necrosis factor-α, and malondialdehyde levels and increased (P < 0.05) the levels of immunoglobulin G, jejunal mucin 2, total antioxidant capacity, and total superoxide dismutase. GML down-regulate (P < 0.05) jejunal interleukin-1β and interferon-γ expression and increased (P < 0.05) the mRNA level of zonula occludens 1 and occludin. A reduced (P < 0.05) expression of toll-like receptor 4 and nuclear factor kappa-B was shown in GML-treated groups. In addition, GML modulated the composition of the cecal microbiota of the broilers, improved (P < 0.05) microbial diversity, and increased (P < 0.05) the abundance of butyrate-producing bacteria. Spearman’s correlation analysis revealed that the genera Barnesiella, Coprobacter, Lachnospiraceae, Faecalibacterium, Bacteroides, Odoriacter, and Parabacteroides were related to inflammation and intestinal integrity. In conclusion, GML ameliorated intestinal morphology and barrier function in broiler chicks probably by regulating intestinal immune and antioxidant balance, as well as intestinal microbiota.